Social media addiction and academic engagement: the role of sleep quality and fatigue among university students in Somalia - Khalaf, Mohamed A. A.; Omar, Abdifetah Ibrahim; Abdulle, Abdirizak Warsame; Mohamud, Mohamed Ahmed (Frontiers in Education, 2025)
PurposeA growing concern over social media addiction (SMA) and its impact on academic performance has highlighted a need to understand the underlying mechanisms. While a negative correlation is established, the pathways of influence remain unclear. This study examines the mediating roles of sleep quality and fatigue in the relationship between SMA and academic performance among university students in Somalia.MethodsA cross-sectional survey was administered to 566 undergraduate students. The BSMAS, UWES, PSQI, and FAS scales were used to measure SMA, academic performance, sleep quality, and fatigue, respectively. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) to test a model of direct and indirect effects.ResultsThe findings revealed a significant direct negative relationship between SMA and academic performance. Sleep quality emerged as a significant mediator; SMA was linked to poorer sleep, which in turn predicted lower academic performance. In contrast, while SMA was associated with higher fatigue, fatigue was not a significant mediator in the relationship between SMA and academic performance.ConclusionsSMA appears to harm academic performance through two distinct routes: a direct pathway linked to motivational deficits and self-regulation failure, and an indirect pathway via energy depletion from poor sleep. Fatigue is a consequence but not a causal mechanism for academic decline in our model. Educational institutions should implement interventions targeting both sleep quality and digital self-regulation to mitigate the academic consequences of excessive social media use. Future studies employing longitudinal designs could further clarify the causal dynamics of these relationships.